Surgical Management of Vaginal Hyperplasia in a Labrador Bitch - Gangwar, Chetna; Jajriya, Omprakash; Sobhit; Mishra, Renuka; Kumar Yadav, Brijesh (The Indian Journal of Animal Reproduction, 2026)
A 2.5-year-old female Labrador was presented to the Veterinary Clinical Complex, with a history of a large (8 x 4 cm) tongue shaped mass protruding from the vulva for the past two weeks. Clinical evaluation revealed a prominent, red, pedunculated, semisoft mass emerging from the vulvar lips, which was non-painful on palpation. Based on clinical find ings and confirmed through histopathological examination, the condition was diagnosed as vaginal hyperplasia. The prolapsed tissue was surgically excised with successful outcome.